2014
DOI: 10.1177/096739111402200101
|View full text |Cite
|
Sign up to set email alerts
|

Curing Kinetics and Thermal Properties of Aromatic Multifunctional Epoxy Resins

Abstract: In order to investigate the relationship between the chemical structure of multifunctional epoxy resins and their properties, two tetrafunctional epoxies with different aromatic rings content in the molecular main chain, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenyl ether (4,4'-TGDDE) and N,N,N',N'-tetraglycidyl-2,2-bis[4-(4-aminophenoxy)phenyl]propane (TGBAPP), were cured with 4,4'-diaminodiphenyl ether (4,4'-DDE) and 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), respectively. Then four amine curing systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This is supported by the dynamic DSC results also in Table , which indicate that T p , the temperature at the peak rate of reaction, decreases consistently with increasing para substitution, again regardless of hardener, indicating a faster cure reaction. Support for these results comes from Yu et al using a related tetrafunctional amino glycidyl epoxy resin cured with MNA who also reported a modest increase in reaction rate as aromatic substitution changed from meta to para. The total enthalpies during cure, both dynamic and isothermal in Table reveal an overall decrease in enthalpy with increasing para substitution regardless of hardener.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…This is supported by the dynamic DSC results also in Table , which indicate that T p , the temperature at the peak rate of reaction, decreases consistently with increasing para substitution, again regardless of hardener, indicating a faster cure reaction. Support for these results comes from Yu et al using a related tetrafunctional amino glycidyl epoxy resin cured with MNA who also reported a modest increase in reaction rate as aromatic substitution changed from meta to para. The total enthalpies during cure, both dynamic and isothermal in Table reveal an overall decrease in enthalpy with increasing para substitution regardless of hardener.…”
Section: Resultsmentioning
confidence: 89%
“…Patel et al synthesized novel tetrafunctional epoxy resins consisting of four aromatic rings linked via two ether groups and different central groups such as phenyl, isopropyl, and cyclo‐hexyl but mostly compared the effect of different hardeners rather than the impact of the structural variation of the epoxy resin on the properties. Yu et al also explored the synthesis and cure of a similar four membered tetrafunctional epoxy resin with two ether links and a central isopropyl group, with both aromatic amine and anhydride hardeners. They concluded that introducing more aromatic rings decreased the rate of cure but enhanced thermal properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multifunctional epoxy resins contain three or more epoxy groups, which are incorporated into the epoxycured system by reaction with the curing agent. [18][19][20][21] Multifunctional epoxy resins are mainly used as modifiers and matrix resins to obtain cured epoxy resin products with special properties, such as higher mechanical properties, glass transition temperature (T g ) value, heat resistance, and dielectric properties. Thomas et al [22][23][24] reported a series of biobased thermoset epoxides, such as acid-cured norbornylized seed oil epoxides, new epoxidized vegetable oils-based thermosets, biobased methacrylate epoxidized-thermosets, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional epoxy resins contain three or more epoxy groups, which are incorporated into the epoxy‐cured system by reaction with the curing agent 18–21 . Multifunctional epoxy resins are mainly used as modifiers and matrix resins to obtain cured epoxy resin products with special properties, such as higher mechanical properties, glass transition temperature ( T g ) value, heat resistance, and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%